Prediction of global potential distribution and assessment of habitat suitability for Xanthium spinosum driven by climate change - Fan, Yuke; Zhang, Xiaowei; Yang, Junlong; Yang, Jun; Zhang, Hongmei; Yang, Bo; Li, Xiaowei (Frontiers in Plant Science, 2025)
Xanthium spinosum Linn (Asteraceae family), native to South America, is among the most invasive plant species globally, with major ecological, agricultural, and livestock-related impacts. However, little is known about how climate change may alter its future distribution and range shifts. This study assessed the potential global distribution and habitat suitability of X. spinosum by evaluating its dispersal risk under climate change. We compiled 13,378 global occurrence records and applied the MaxEnt model (optimized via the R package ENMeval) to simulate habitat suitability under current conditions and three future climate scenarios (SSP126, SSP370, and SSP585) for 2040–2060, 2060–2080, and 2080–2100. The model performed with high accuracy (area under the curve > 0.979). The most influential factor was the minimum temperature of the coldest month (Bio6; 67.1% contribution), with an optimal range of −7.3 °C to 8.7 °C. Other key drivers included Bio10, Bio19, and Bio7. Currently, core suitable areas include western North America to central/western Europe, southeastern South America to West Africa, and Southeastern Australia to East Asia, spanning 2,950.42 × 104 km2 (52.8% of potential distribution). Under SSP126, suitable habitats expand steadily (+338.15 × 104 km2 by 2080–2100). SSP370 projects large fluctuations, peaking at + 448.26 × 104 km2 in 2060–2080. SSP585 predicts rapid early expansion (+392.54 × 104 km2 by 2040–2060), with the rate of expansion decreasing in the mid and late stages. These findings support invasion risk assessment, early warning development, and targeted management strategies for X. spinosum in a changing climate.